Paleomagnetic recording fidelity of nonideal magnetic systems - Adrian R. Muxworthy; David Krása; Wyn Williams; Trevor P. Almeida (Geochemistry, Geophysics, Geosystems)
Abstract A suite of near‐identical magnetite nanodot samples produced by electron‐beam lithography have been used to test the thermomagnetic recording fidelity of particles in the 74–333 nm size range; the grain size range most commonly found in rocks. In addition to controlled grain size, the samples had identical particle spacings, meaning that intergrain magnetostatic interactions could be controlled. Their magnetic hysteresis parameters were indicative of particles thought not to be ideal magnetic recorders; however, the samples were found to be excellent thermomagnetic recorders of the magnetic field direction. They were also found to be relatively good recorders of the field intensity in a standard paleointensity experiment. The samples' intensities were all within ∼15% of the expected answer and the mean of the samples within 3% of the actual field. These nonideal magnetic systems have been shown to be reliable records of the geomagnetic field in terms of both direction and intensity even though their magnetic hysteresis characteristics indicate less than ideal magnetic grains.